SOLUBILITY OF THE ASSEMBLAGE ALBITE+K-FELDSPAR+ANDALUSITE+QUARTZ IN SUPERCRITICAL AQUEOUS CHLORIDE SOLUTIONS AT 650 °C AND 2 KBAR - Pak T.M.; Hauzenberger C.A.; Baumgartner L.P. (My University, 2003)
The solubility of the high grade pelite assemblage albite+K-feldspar+andalusite+quartz at 650 °C and 2 kbar was determined in aqueous solutions over a total chloride range of 0.01-3 mClt°t using rapid-quench hydrothermal technique. The concentration of Na, K, Si, and Al was determined in the fluid phase after quench. The K/Na ratio was determined by approaching the equilibrium from below and above. It is 0.34 at low chloride concentrations and decreases slightly to 0.31 with increasing total chloride. Silica and aluminum concentrations were determined only from undersaturation. The silica solubility is found to be independent of chloride concentration and is ~0.13 molal. Aluminum is nearly independent of chloride concentration decreasing only slightly from ~0.0015 to ~0.0007 molal. Comparison of the experimental data with thermodynamic model calculations demonstrates that the silica concentrations are well predicted, while significant differences exist between individual databases for Al speciation and its total concentration. Al concentrations are underestimated by up to 10 to 15 orders of magnitude using the SUPCRT92 database. Predicted K/Na ratios are underestimated by up to 30%. The best predictions achieved for this simplified high-grade pelite assemblage are those using the SUPCRT92 database with revised thermodynamic data for feldspars and K- and Na-species (J. Phys. Chem. Ref. Data 24 (1995) 1401) and additional Al-species (Am. J. Sci. 295 (1995) 1255; Geochim. Cosmochim. Acta 61 (1997) 2175). The use of ideal mixing for neutral complexes in combination with the extended Debye-Huckel activity model for the charged species yields the most compatible speciation model.
Keywords: SOLUBILITY; SUPERCRITICAL; CHLORIDE SOLUTIONS; ALBITE; K-FELDSPAR